Did J. P. Morgan's Men Add Liquidity? Corporate Investment, Cash Flow, and Financial Structure at the Turn of the Twentieth Century - RAMIREZ, CARLOS D. (Journal of Finance, 1995)
ABSTRACT This article presents evidence suggesting that the relationship that existed between the partnership of J. P. Morgan and its client firms partially resolved the latter's external financing problems by diminishing the principal‐agent and asymmetric information problems. I estimate and compare investment regression equations for a sample of Morgan‐affiliated companies and a control group of nonaffiliated companies. The econometric results seem to indicate that companies not affiliated to the House of Morgan were liquidity constrained.